FAKTOR TEKNIS YANG BERPENGARUH TERHADAP HASIL TANGKAPAN UTAMA PUKAT UDANG DI LAUT ARAFURA - Daniel Rezki; Ronny Irawan Wahju; Mulyono S Baskoro; Muhammad Imron (Jurnal Teknologi Perikanan dan Kelautan, 2014)
Shrimp is an economic important commodity in fishery with shrimp trawl as the most effective fishing gear. One of effort to maximize the number of shrimp catch is the application of the technical factors which significantly influence the catch rate of shrimp. Method of this research was observational. The purpose of this research was to analyze the influence of fishing time (day and night), towing speed, and towing duration towards shrimp catch rate. The result of this research are night operation has greater catch rate (24.10 ± 9.60 kg/hour, the effective tow duration is 91-150 minutes (46.78 ± 22 kg/hauling) and towing speed with greater catch rate is 2.50-3.00 knot (13.18 ± 3.30 kg/hour). The results of the analysis should that factors can maximize the catch of shrimp trawl.